Dopamine D3 Receptors Inhibit Hippocampal Gamma Oscillations by Disturbing CA3 Pyramidal Cell Firing Synchrony - Lemercier, Clément E.; Schulz, Steffen B.; Heidmann, Karin E.; Kovács, Richard; Gerevich, Zoltan (Frontiers in Pharmacology, 2016)
Cortical gamma oscillations are associated with cognitive processes and are altered in several neuropsychiatric conditions such as schizophrenia and Alzheimer’s disease. Since dopamine D3 receptors are possible targets in treatment of these conditions, it is of great importance to understand their role in modulation of gamma oscillations. The effect of D3 receptors on gamma oscillations and the underlying cellular mechanisms were investigated by extracellular local field potential and simultaneous intracellular sharp micro-electrode recordings in the CA3 region of the hippocampus in vitro. D3 receptors decreased the power and broadened the bandwidth of gamma oscillations induced by acetylcholine or kainate. Blockade of the D3 receptors resulted in faster synchronization of the oscillations, suggesting that endogenous dopamine in the hippocampus slows down the dynamics of gamma oscillations by activation of D3 receptors. Investigating the underlying cellular mechanisms for these effects showed that D3 receptor activation decreased the rate of action potentials during gamma oscillations and reduced the precision of the action potential phase coupling to the gamma cycle in CA3 pyramidal cells. The results may offer an explanation how selective activation of D3 receptors may impair cognition and how, in converse, D3 antagonists may exert pro-cognitive and antipsychotic effects.